Following up the Discussion on the stricto sensu ‘Principles’ in Modern International Law, and Beyond the Same …. - L. P. Anufrieva (Московский журнал международного права, 2021)
INTRODUCTION. The situation in domestic legal science of Russia in the field of research of the subject of principles in international law may be ascertained in general terms as a fairly static picture that inspires a serene belief in the immutability of the existing position and further stable sustainability thereof. Such state of things consists in the illusion of the non-availability of difficulties or problems – a person starts from the point of a binary opposition in the values of principles / norms, as well as the unchangeable existence of the dichotomy of basic and sectoral principles. At the same time, let’s take note, that sectoral principles are alternatively and in most cases equivalently treated as special ones [Chernichenko 2014:101-102]. The implications of the said assumption are ideas relevant to sectoral principles as based on the presumption of their similarity in essence and function, based only on the name and place in the regulatory system (branch of law). Undoubtedly, the general tendencies for the sectoral principles of the International Law (IL) are those, which, firstly, appear like basic ones, objectively, and, secondly, the lists and scope thereof depend from specific relations immune to particular branches of law. At the same time, with due account to the submissions afore-referred, the affected area is in many aspects significantly various, not simple and can give rise to many differing views, discussions, objections, rejection or support, etc., because it is conditioned by the real fact of availability in international law of a greater variety of substances/ other phenomena in the matter of principles. Due to the above, a more meticulous view of the principles in international law shall be required: on the one hand, revealing the rationale for the fact that they are not a chaotic phenomenon within the system of international law, and, on the other hand, providing a substantive analysis of them, taking into account the differentiation and identification of objects that claim to be placed under the head of principles, construing the typology thereof, etc. Such an approach is not only assumed as logical, but prima facie due by time and, therefore, fully justified.MATERIALS AND METHODS. The article is based on the provisions of international treaties, materials of codification of international law norms by the UN International Law Commission, judicial decisions, acts of law enforcement of the International Court of Justice or other international courts, and documents embodying the positive international law, as well as the teachings of the most highly qualified publicists in the field of theory and practice of international law. The research operates with various general and particular methods of analysis: dialectical materialism, structural and system analysis, formal logic, deduction and induction, comparative law, historical and retrospective approach, formal legal analysis, legal modeling, “techniques of evidence” (legal reasoning), as well as various methods of legal interpretation, etc., adopted in domestic and expatriate jurisprudence.RESARCH RESULTS. The purpose of this publication is to endeavor certain clarification of theoretical data related to such a fundamental category as “the principle of international law”, which is deemed to canbe achieved through proper identification of various constructions that operate with the element “principles” or similar terms, by way of systematization and delineation thereof from other phenomena available in the framework of international legal reality. Therefore, it is not occasional that the title of the article operates with such a formula to designate the discourse: “…. on the stricto sensu ‘principles’ in modern international law and beyond...”. To ensure the better links of the scope and objectives of the research in terms of highlighting the system of principles and smooth functioning both of international law itself and the entirety of its principles and norms, as well as to clarify and streamline the basic terminology and conceptual basis of international legal science in the matter of principles, the typology of concepts that form the legal backgrounds for contemporary regulation of interstate relationships has been commissioned herein, since there is heterogeneity of various heads of items that claim to be the principles of international law, even with no normative nature in some of them, etc. The same appears to be quite obvious facts. In witness of the same, there are, on the one hand, diversification of the normative principles expressed in modern international law, which determines the identifying features for each of existing heads of principles, and as an outcome of the latter, the need to build up the respective system, on the other hand. However, the grounds for “stratification”, i.e. the distribution of the principles per separate groups (for example, the subdivision into basic and sectoral principles or differentiation between the system-wide and special principles), are far from being exhaustively revealed as yet, and need in better targeted efforts of scholars. Due to the above, the author held differentiating sectoral and special principles inter se, having substantiated the segregation of the specific head of principles within the latter group – “principles of autonomous (self-contained) legal regimes”.DISCUSSION AND CONCLUSIONS. It seems that there is a serious substantive distinction between the formula “principles of modern international law” and “principles in modern international law”. The discourse outlined as “principles in international law”, having a broader sense and destination, in the absence of an unambiguous understanding of the term ‘the principle’, is more diligent to reflect the state of things in the field of principles in so far the legal science / international law science is concerned regarding the essence, features, and functional qualities of any particular type of objects, sometimes referred to as ‘principles’. In case, if it comes to “principles of international law”, they are to be identified primarily as the fundamental, guiding, hierarchically high norms within the system of international law, bearing the burden of the most important components of this system, and are classified according to generic and specific characteristics, which depend on their salient features. The formula “principles in international law” assumes a view of of the subject that has a broader and less structured range of options for qualifications.